Teaching Beyond Tradition: Building Teacher Agency in Multilingual EFL Classrooms - Regmi, Lok Raj; Acharya, Resham (International Journal of Language and Literary Studies, 2025)
This paper focuses teacher agency for multilingual pedagogy. Drawing on lived experiences of two community school teachers, we discuss how teachers, going beyond the tradition, build teacher agency in multilingual EFL classrooms to address the needs of the students and necessity of the classroom environment. The findings of the study reveal that teachers negotiate with English only policy in a unique way integrating multilingual realities of the classroom. By using learners’ home language in classrooms, the teachers address various classroom challenges such as incomprehensibility of content in English only class, students’ feeling of exclusion, and so on; and ensure the right of the students for education. The findings also reveal that teachers practice various multilingual activities (such as code switching, translation and so on) in English classrooms. The findings, further, show that teachers practice such activities by utilizing their own personal and professional biographies.